An in vitro investigation of the effect of Khellin and UVA (KUVA) on normal and transformed human melanocytes - Carlie, Gadija (Department of Human Biology, 2018)
The problematic and numerous side effects of PUVA (psoralen and UVA) and other treatments currently in use for vitiligo, have justified the search for an alternative treatment. In this study, the use of khellin, a naturally occurring furochromone, which is similar in structure to psoralens, is explored as an alternative treatment for vitiligo. When khellin is combined with UVA (KUVA), it is reported to repigment vitiligo skin as effectively as PUVA photochemotherapy, but without the adverse effects reported with PUVA. The exact mechanism for khellin-induced repigmentation is still to be determined and no cell biological studies have yet been done to elucidate its mechanism of action. The specific aim of this project was to set up an in vitro tissue culture system to determine the direct effects of khellin, UVA and KUVA on melanocyte proliferation and pigmentation. Studies were carried out on cultures of a human melanoma cell line (Mel-1), normal human melanocytes and 3T3 mouse fibroblasts. Cell proliferation assays revealed that the proliferation of melanoma cells and melanocytes were increased after exposure to khellin for four days at concentrations ranging from 1nM to 0.5mM. A peak of proliferation was obtained at 0.01mM khellin, which stimulated proliferation of melanoma cells and melanocytes by 2.3 5-fold and 2.1- fold, respectively. In contrast, khellin decreased proliferation of fibroblasts over the entire concentration range tested. At concentrations of 0.5mM and above, khellin was cytotoxic to both melanocytic cells and fibroblasts. Cytotoxic assays revealed that 1mM khellin was equally cytotoxic to both melanoma cells and fibroblasts. In addition, these assays revealed that the proliferative response observed with 0.01mM and 0.1mM khellin, did not mask an underlying cytotoxic effect. Exposure to single doses of UVA between 150-280mJ/cm², increased proliferation of melanoma cells with maximal proliferation at 250mJ/cm², while the proliferation of normal melanocytes and fibroblasts were unaffected by this UVA dose. More significantly than khellin or UVA alone, the treatment with the combination of khellin and UVA (KUVA) stimulated proliferation of the melanocytic cells. The combination of 0.01mM khellin plus a single dose of UVA at 250mJ/cm² was the most effective treatment. KUVA combination treatments were found to be more cytotoxic to the fibroblasts than khellin or UVA alone. To test the effect of khellin, UVA and KUVA on melanogenesis, standard radiometric assays were carried out. The combination of khellin and UVA enhanced melanogenesis of the melanocytic cells more significantly than khellin alone or UVA alone. The dose of 0.01mM khellin plus 250mJ/cm² UVA (maximal proliferative dose) increased melanogenesis of the melanocytes by 290% above the untreated control melanocytes. To determine whether khellin and KUVA act by increasing levels of melanogenic proteins, western blot analyses were carried out. The results revealed that there were no differences in the amounts of TRP-2 and tyrosinase in the melanocytic cells treated with khellin alone. In contrast, those treated with KUVA (or UVA alone) had increased levels of the glycosylated form of the enzymes and also possibly had increased levels of the de nova form of the enzymes. These results suggest that UVA might be enhancing glycosylation of melanogenic enzymes and provides a novel insight into the possible mechanism for UVA-induced melanogenesis. The results also revealed that 3T3 fibroblasts expressed the non-glycosylated form of TRP-2, as described by others. In conclusion, this study suggests a model in which khellin acts directly on melanocytic cells by acting as a mitogen and a melanogen at non-toxic concentrations. Khellin possibly increases melanogenesis by acting post-translationally or antagonizing or removing an inhibitor of the melanogenic pathway. The melanocyte-specific effect of khellin and even more so KUVA, seems to suggest that khellin acts along the signal transduction pathways which increases both proliferation and melanogenesis in melanocytes, possibly via endothelin-1 pathways.